Self-Perception of Changes in Routines in Adults and Older Adults Associated to Social Distancing Due to COVID-19—A Study in São Paulo, Brazil - Machado-Lima, Adriana; Alonso, Angélica Castilho; Gozzo, Débora; Zanca, Gisele Garcia; Brech, Guilherme Carlos; Montiel, José Maria; Bastos, Marta Ferreira; Longo, Priscila Larcher; Mota-Ortiz, Sandra Regina (Frontiers in Psychology, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a RNA virus related to COVID-19, an acute respiratory illness with higher mortality in older adults. This condition is spread person-to-person through close contact and among policies employed to decrease transmission are improvement of hygiene habits and physical distancing. Although social distancing is recognized as the best way to prevent the contamination, there are concerns it may promote the increased depression symptoms risk and anxiety, mainly in older adults. This cross-sectional study aimed to verify self-concept of social distancing in adults compared to older adults. All participants, over 18 years, residents of São Paulo state (Brazil), were invited to join this research study by a message application and answered an interdisciplinary questionnaire during the period from May 23rd to June 23th 2020. The questions were divided in the following aspects: sociodemographic data, financial conditions and routine-related perception; perception of health, physical and emotional state; and eating habits. The adults group was composed by 139 participants, with mean age of 43.15 years (±10.92), and the older adults group was composed by 437 participants with mean age of 67.59 years (±6.13), of both sex. Changes in routine during the period of social distance were reported by 95% of adults and 96.8% of older adults but adults indicated more significant alterations in routine. Although there was no difference between groups for several aspects, adults revealed greater alterations in sleep quality, evacuation frequency, and more difficulty to perform daily activities at home. Further studies are necessary to follow up the impacts of social distancing among adults and older adults in different socioeconomic contexts to better understand the long-term alterations and the necessity of interventions.